AMP-Activated Protein Kinase Regulation of the NLRP3 Inflammasome during Aging. (January 2018) - Cordero, Mario D.; Williams, Matthew R.; Ryffel, Bernhard
Abstract : The NLRP3 inflammasome has recently emerged as an unexpected marker of stress and metabolic risk and has also been implicated in the development of major aging-related diseases such as gout, type 2 diabetes, obesity, cancer, and neurodegenerative and cardiovascular disorders. Several pathways regulating the NLRP3 inflammasome are currently being studied, but how the NLRP3 inflammasome is regulated remains unknown. AMP-activated protein kinase (AMPK), a central regulator of multiple metabolic pathways involved in the pathophysiology of aging and age-related diseases, has emerged as an important integrator of signals controlling inflammation including the inflammasome. In this Opinion article, we show that several AMPK-dependent pathways regulate NLRP3 inflammasome activation during aging, suggesting NLRP3 as a potential pharmacological target in age-related diseases. Trends: AMP-activated protein kinase (AMPK) and the NLRP3 inflammasome are associated with aging and age-related diseases through the disturbance of metabolic and inflammatory pathways. Many of the various NLRP3 inflammasome stimuli, such as mitochondrial and autophagy dysfunction and endoplasmic reticulum stress, become elevated during the aging process. The AMPK–sirtuin 1 (SIRT1) axis could modulate the inhibition of NLRP3 by mitochondrial biogenesis and the induction of autophagy. Inhibition of NLRP3 is also induced through various antiaging strategies such as metformin, rapamycin, or resveratrol treatment and caloric restriction.